2002
DOI: 10.1089/107632702760184709
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-Transduced Human Fibroblasts Convert to Osteoblasts and Form Bonein Vivo

Abstract: Experimental cell or ex vivo gene therapy for localized bone formation typically uses osteoprogenitor cells propagated from periosteum or bone marrow. Both require bone or marrow biopsies to obtain cells. We have demonstrated that implantation of gingival or dermal fibroblasts transduced with BMP ex vivo, using a recombinant adenovirus (AdCMVBMP) attached to porous biodegradable scaffolds, form bone in vivo. Here we show that BMP-7-transduced fibroblasts suspended in injectable thermoset hydrogels form complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 37 publications
4
144
1
Order By: Relevance
“…Recent studies have investigated the ability of cells committed to a fibroblastic lineage to undergo osteogenic differentiation. Specifically, human gingival and dermal fibroblasts were able to express osteoblast differentiation markers after transduction with vectors overexpressing BMPs [38,50,76]. Human dermal fibroblasts cultured on ultraporous b-tricalcium phosphate ceramics demonstrated increased osteogenic differentiation [36].…”
Section: Design Considerations For Functional Tissue Engineering Of Pmentioning
confidence: 99%
“…Recent studies have investigated the ability of cells committed to a fibroblastic lineage to undergo osteogenic differentiation. Specifically, human gingival and dermal fibroblasts were able to express osteoblast differentiation markers after transduction with vectors overexpressing BMPs [38,50,76]. Human dermal fibroblasts cultured on ultraporous b-tricalcium phosphate ceramics demonstrated increased osteogenic differentiation [36].…”
Section: Design Considerations For Functional Tissue Engineering Of Pmentioning
confidence: 99%
“…Studies using cells for bone regeneration have demonstrated that the seeded cells could not only provide an osteogenic cell source for new bone formation, but also secrete growth factors to recruit native cells to migrate into the defect site. [19][20][21] Although many kinds of derived stem cells besides bone have been studied, such as adipose, 20 muscle, 21 and skin, 22 we concluded that bone marrow stem cell is the best candidate seeded cell for bone-engineering by our previous studies in animal models. 15,18,[23][24][25][26] Local gene therapy systems have the potential to provide more sustained protein production, deliver protein in a physiologic manner, and allow for the development of biological cellular delivery vehicles that can enhance bone repair.…”
Section: Discussionmentioning
confidence: 97%
“…Passage 4 fibroblasts were infected with AdCMV-BMP-7, a recombinant adenovirus construct expressing the murine BMP-7 gene under a cytomegalovirus (CMV) promoter [42]. Such infected primary cells have been shown to form bone in vivo [43][44][45][46][47][48][49]. Two million cells were seeded into each scaffold by suspending them in 30 jil of 2 mg/ml collagen gel made from acid-solubilized rat tail collagen (BD Biosciences, Bedford, MA), which was gelled using 37 0 C incubation [50].…”
Section: Cell Seeding and Implantationmentioning
confidence: 99%